Tata Sons: Power, Governance, and Leadership in a Trust-Controlled Conglomerate (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In October 2016, Tata Sons found itself at the centre of an unexpected leadership crisis when Cyrus P. Mistry was removed as Chairman. What followed was not just a corporate dispute, but one of the most widely debated governance episodes in modern Indian business. The situation offers a compelling lens to understand how power, leadership, ownership, and institutional structures interact within large business groups (Chakrabarti et al., 2008; Tricker, 2019).Tata Sons represents a distinctive organizational form. Unlike many global corporations, it operates as a professionally managed conglomerate with a majority ownership held by philanthropic trusts. This arrangement has historically supported long-term thinking and ethical governance, but it also creates complex and sometimes ambiguous lines of authority between trustees, board members, executives, and minority shareholders (Khanna & Palepu, 2010; OECD, 2015). Recent work suggests that such hybrid ownership models can be both a strength and a source of governance tension, particularly in emerging market contexts (Singh & Delios, 2023).What makes the Tata–Mistry episode particularly significant is how several forces converged at once—leadership succession, concentrated ownership, and boardroom dynamics—each reinforcing the other. Formal governance mechanisms existed, but informal influence, legacy considerations, and relational power played an equally important role in shaping outcomes (Pfeffer, 2010; Mintzberg, 1983). The episode raised uncomfortable but important questions about board independence, transparency, and the actual autonomy available to professional leaders in legacy-driven organizations (Aguilera et al., 2021).